Better together : making church mergers work - Tomberlin, Jim; Leadership Network (Dallas, Tex.) (San Francisco, CA : Jossey-Bass, a Wiley Imprint, 2012)
"Thousands of Protestant churches are perplexed by plateaued or declining attendance, while other congregations nearby thrive. Is there a way for them to combine forces, drawing on both their strengths, in order to increase their missional impact? Church merger consultant Jim Tomberlin (with co-writer Warren Bird) makes the case that mergers today work best not with two struggling churches but with a vital, momentum-filled lead church partnering with a joining church. In this practical, example-filled, hands-on guide for church leaders at all levels, they enable those contemplating mergers to understand the issues, avoid landmines, and develop strategies for success"--
God is doing something new: biblical basis for mergers -- Four models for healthy mergers -- Missional, multisite, multiethnic, and other merger motives -- Stages and speed of a merger -- How to measure success -- Why mergers fail -- Financial and legal aspects of a merger -- Personnel changes -- Determining whether your church is a good merger candidate -- How to start the merger conversation -- Self-assessment for merger readiness -- Exercise: identifying your merger issues -- Managing pain and change -- Where do you go from here? -- Appendixes.
"A Leadership Network publication."
Includes bibliographical references (pages 233-240) and index.
Keywords: Christian union